Pentraxin 3 Plasma Levels and Disease Activity in Systemic Lupus Erythematosus. (3rd November 2015) - Assandri, Roberto; Monari, Marta; Colombo, Anna; Dossi, Alessandra; Montanelli, Alessandro
Abstract : SLE is an autoimmune disorder that involves polyclonal autoimmunity against multiple autoantigens. PTX3, a marker of the acute-phase inflammatory response, plays an important role in innate immunity and in modulation of the adaptive immune response. Our study tried to resolve some rather controversial aspects of the use of PTX3 as a biomarker of disease activity in SLE patients. We demonstrated that plasma PTX3 concentration of the SLE patients was significantly higher than the healthy control groups and reflected disease activity. ROC curve analysis was used to determine best cut-off point (2.8 ng/mL) with a good sensitivity and specificity. In patients with SLE, PTX3 concentrations were correlated with SLEDAI. Trend to remission (TTR) curve was created by plotting PTX3 levels and SLEDAI and we applied the curve as a model for the analysis of two patients with different follow-up. PTX3 plasma levels declined significantly and this decline occurred parallel to the clinical improvement with a complete remission of disease. In patients who experienced a clinical relapse, an increase in PTX3 levels followed the lupus flare. The proposal of PTX3 cut-off associated with TTR and monitoring of PTX3 plasma levels could be an innovative approach to follow-up of SLE patients.